EFEKTIVITAS PENERAPAN PENDIDIKAN MATEMATIKA REALISTIK TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMK NEGERI 1 BATANG ANGKOLA - Fatimah Siregar; Eva Yanti Siregar; Marzuki Ahmad (JURNAL MathEdu (Mathematic Education Journal), 2020)
abstract The aims of this study is to describe the effectiveness of using Realistic Mathematical Education (RME) approach on students’ mathematical problem solving ability on the topic of the system of linier equation two variables at the tenth grade students of SMK Negeri 1Batang Angkola. This research was conducted by applying experimental method with 30 students as the sample and they were taken by using simple random sample technique from 130 students. Test and observation were used in collecting the data. Based on descriptive analysis, it was found (a) the average of using RME approach was 2.8 (good category) and (b) the average of students’ mathematic problem solving ability on the topic of the system of linier equation two variables before using RME approach was 49.9 (poor category) and after using RME approach was 85.9 (very good category). Furthermore, by using pair sample ttest and help SPSS version 17, the result showed the significant value was less than 0.05 (0.000<0.05). It means, RME approach was effective used on students’ mathematic problem solving ability on the topic of the system of linier equation two variables at the tenth grade students of SMK Negeri 1Batang Angkola. Keywords: RME approach, mathematical problem solving ability, the system of linier equation two variables